Augur Augurem Videns... Belief and Make-Believe in Social Life - Wojciech Żełaniec (Rosenberg & Sellier, 2016)
Lévy-Bruhl thought that the primitive mind could not really distinguish itself from the ‘collective mind’ of the community it was immersed in; the post-modern mind, by contrast, though arguably no less forcibly pressed into the Procrustean bed of various collective beliefs, is very well in the position to dissociate itself from the ‘us’ whose position it sometimes pretends to represent. Are such beliefs, then, really anyone’s beliefs or are they merely ‘make-believes’? Though Gilbert in her ‘Joint commitment’ does not explicitly address this question, I try to reconstruct, from the text of her book, her possible answer to it.